9. BITCOIN AS A SYSTEM THAT RESISTS RECOVERY A NON-LINEAR SYSTEM DESIGN STUDY ON SCARCITY AND SECURITY - Farrid Hidayat; Suroso; Kurniawan; Hidayad; Muchammad Furqon; Farrith; Dikatamasania; Sudibiyo (Jurnal TNI Angkatan Udara, 2026)
This study aims to structurally examine why loss of access to Bitcoin is permanentand to assess claims regarding the possibility of recovery, master keys, or backdoors in theBitcoin system. This study departs from the general trend that positions Bitcoin solely as amonetary innovation, while its most radical aspect lies in its system design. Bitcoin is analyzedas a non-linear formal system that defines ownership through cryptographic facts, rather thanthrough identity, intent, or social context. The methodology used is a conceptual-design analysisbased on cryptographic studies, protocol architecture, empirical precedents of human error, andthe implications of network consensus. The main results demonstrate that irreversibility and lossof access are not system failures, but rather direct consequences of Bitcoin's design axioms,which tie ownership to high-entropy private keys and reject all forms of discretionary authority.The analysis also shows that claims of backdoors, whether mathematical, implemental,hardware, or temporal, are structurally incoherent without undermining the fundamentalassumptions of cryptography and decentralized consensus. The study's conclusions affirm thatBitcoin's resilience stems not from adaptive flexibility but from deliberate rule rigidity. Thisresearch's contribution lies in mapping Bitcoin as a system design artifact that resists recovery,while also expanding the Bitcoin discourse from the monetary realm to the study of systemdesign, applied cryptography, and the philosophy of technology.